Chromosomal Genotype in Breast Cancer Progression: Comparison of Primary and Secondary Manifestations - Katrin Friedrich; Theresa Weber; Jens Scheithauer; Wolfdietrich Meyer; Gunter Haroske; Klaus Dietmar Kunze; Gustavo Baretton (Cellular Oncology)
The purpose of this study was to compare the chromosomal genotype between breast cancers with and without secondary manifestations and between primary tumors and their secondary manifestations. Eighty six breast cancers, twenty lymph node metastases, ten distant metastases and ten local recurrences were analyzed by comparative genomic hybridization. Tumors with local recurrences showed significant more frequent losses at 2q32 than the tumors without recurrences. Lymph node positive cases showed significant more frequent losses at 9p21 than node negative cases. Lymph node metastases exhibited significant more frequent losses at 7q11, 14q24.3–q31 and 17q22–q24 than their primary tumors. In cases with distant metastases, losses at 5q23 were more frequent than in those without, but not reaching the significance level. The distant metastases showed significant more frequent losses at 5p15, 12q24 and 17q22–q24 than the primary tumors. These results reveal strong evidence that the potential for progression is determined in the primary tumor and that different ways of the development of local recurrences, lymph node and distant metastases exist. After confirmation of the results by interphase FISH on tissue micro arrays, the detection of these specific chromosomal imbalances may contribute to a more individual prediction of prognosis in breast cancer.